Análise de acurácia entre modelos odontológicos impressos com diferentes resinas e técnicas de prototipagem rápida e modelos convencionais em gesso - Silva, Carlos Augusto Gomes da (2022)
The aim of the study was to measure the accuracy and precision of dental models printed from digital files on 3D printers with different resins and systems. From a dental model, conventional impressions were made with Impregum Soft, and intraoral scanning with the Omnican AF device. The impressions resulted in 10 models of special type IV plaster, while the digital file generated 40 models of each system: Steriolithography (SLA), Digital Light Processing (DLP) and Liquid Crystal Display (LCD). Three printing variables were evaluated: model angle (horizontal or inclined), resin type (three reference and one universal) and the printing system (SLA, DLP or LCD), totaling 12 combinations and a total of 120 models. All impressions were made at 50 μm in the Z axis. The height and width of the clinical crown of teeth 16, 14, 12, 21 and 25 were measured; and the dimension of the arch through points fixed in the canines and first molars. The intraclass correlation coefficient (ICC) between evaluators was greater than 0.980. The RMS (root mean square) was calculated in relation to the master model (accuracy) and in relation to the plaster model (precision). The comparison between the different groups was performed using Student's t test for independent samples (2 groups) or Analysis of Variance (ANOVA) test followed by Tukey's post hoc test (3 or more groups). The Bonferroni correction modified by Finner was used to adjust the p-values. A 5% significance level was determined. A total of 4800 measurements were performed. The variation of the angulation of the model on the platform did not show significant differences for any of the positions with any system or resin (p>0.05). In the general comparison of the systems, there was greater accuracy and precision in the DLP system than in the SLA (p=0.002) and LCD systems (p=0.007), and no resin was predominant over the others (p=0.08). No statistically significant differences were observed between the reference resins of each system. Universal Dental Cosmos resin (Yller) obtained better accuracy and precision in the DLP system, showing a statistically significant difference for SLA and LCD.